Achieving structural stability of LiCoO2 at high-voltage by gadolinium decoration. (April 2022) - Hao, Shuaipeng; Li, Yunjiao; Wang, Shan; Yang, Jiachao; Tan, Zhouliang; Li, Xiaohui; Shen, Xinjie; Xi, Xiaoming; Zheng, Junchao; He, Zhenjiang
Abstract: Raising the cut-off voltages is the easiest way to approach the theoretical specific capacity of LiCoO2 (274 mAh g −1 ). However, an elevated voltage can lead to severe structural degradation and side-reactions at the electrode/electrolyte interface, therefore the excellent electrochemical performance of LiCoO2 is hardly achievable. Hereby, we adopt the gadolinium modification strategy to simultaneously enhance the structural and interfacial stability of LiCoO2 cathode materials. Introducing gadolinium into the transition metal layers can suppress the layered structure collapse triggered by the irreversible phase transition. The interfacial stability is also significantly improved with the gadolinium oxide coating layer formed on the surface of LiCoO2, which separates the cathode from the electrolyte. Therefore, the gadolinium-modified LiCoO2 exhibits a capacity retention of 82.7% after 100 cycles at 3.0–4.6 V, 0.5C. Moreover, density functional theory (DFT) calculations demonstrate that the gadolinium modification of LiCoO2 shortens the Co–O bond length to inhibit lattice oxygen release and reduce the Li + migration barrier, thus exhibiting a capacity of 149.5 mAh g −1 even at 8C. This research will provide novel insights into the structural and interfacial modification of the high-voltage LiCoO2, making a meaningful contribution towards optimizing the electrochemical performance. Graphical abstract: Image 1 Highlights: The introduction of gadolinium inhibited the H3/H1-3 irreversible phase transition of LCO at high voltage. The modification mechanism was investigated by DFT calculations. The Li + diffusion kinetics of LCO before and after gadolinium modification were studied.